Edge magic labeling of graphs - Manickam K.; Marudai M. (Utilitas Mathematica, 2009)
Yegnanarayanan[4] proved some results by introducing (1,1) Edge magic labeling and raised the following two conjectures and an open problem. 1. The disjoint union of 2t copies of P2, t ≥ 1, has a (1,1) edge magic labeling. 2. The generalised n-crown Cn ⊙ K1, n is (1,1) edge magic. 3. Determine the values of m and n such that mPn is (1,1) edge magic. In this paper we prove the two conjectures and partially settele the open problem raised by him.